2007
DOI: 10.1681/asn.2006111286
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Endothelial Cell Autoantibodies Selectively Activate SAPK/JNK Signalling in Wegener’s Granulomatosis

Abstract: The pathogenic role of anti-endothelial cell antibodies (AECA) in vascular injury is debated. It was previously shown that many patients with Wegener's granulomatosis (WG) have AECA that react with human kidney microvascular endothelial cells (EC). In addition, during active disease, renal endothelium strongly expresses the inflammatory molecules vascular adhesion protein-1 (VAP-1) and MHC class I-related antigen A (MICA). This study sought to determine whether AECA mediates this upregulation of VAP-1 and MICA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Stimulation of human kidney endothelial cells with AECA upregulated vascular adhesion protein-1 (VAP-1), CCL2 (MCP-1), MHC class I-related antigen A (MICA), and CXCL6 (GCP-2) expression. AECA also activated c-Jun, ATF2, and NF- κ B (204). IgA anti-endothelial cell antibodies present in sera from children with active Henoch–Schönlein purpura induce ERK phosphorylation and CXCL8 (IL-8) expression in HUVECs (205).…”
Section: Endothelial Response To Gcs In Vasculitismentioning
confidence: 99%
“…Stimulation of human kidney endothelial cells with AECA upregulated vascular adhesion protein-1 (VAP-1), CCL2 (MCP-1), MHC class I-related antigen A (MICA), and CXCL6 (GCP-2) expression. AECA also activated c-Jun, ATF2, and NF- κ B (204). IgA anti-endothelial cell antibodies present in sera from children with active Henoch–Schönlein purpura induce ERK phosphorylation and CXCL8 (IL-8) expression in HUVECs (205).…”
Section: Endothelial Response To Gcs In Vasculitismentioning
confidence: 99%
“…Accordingly, EC-binding antibodies have been shown to activate cultured EC, as manifested by the expression of adhesion molecules (27). Perry et al (36) found that AECA levels were associated with histological evidence of active renal damage on biopsy specimens, while George et al (24) reported that the presence of AECA could contribute to future EC dysfunction with a resultant prothrombotic tendency.…”
Section: Discussionmentioning
confidence: 99%
“…After in vitro stimulation with antiendothelial cell auto-antibodies from patients with Wegener's granulomatosis, human renal microvascular endothelial cells acquired a proinflammatory phenotype with upregulation of the expression of chemokines and VAP-1. While the proinflammatory effects of anti-endothelial antibodies may be blocked by specific inhibitors of the signaling cascade (such as SAPK/ JNK), VAP-1 overexpression cannot (32).…”
Section: Ssao In Kidney Diseasementioning
confidence: 99%